Antibody response to two doses of inactivated SARS‐CoV‐2 vaccine (CoronaVac) in kidney transplant recipients. Issue 6 (17th October 2021) - Eren Sadioğlu, Rezzan; Demir, Erol; Evren, Ebru; Aktar, Merve; Şafak, Seda; Artan, Ayşe Serra; Meşe, Sevim; Ağaçfidan, Ali; Çınar, Güle; Önel, Mustafa; Karahan, Zeynep Ceren; Şengül, Şule; et al.
Abstract: Background: Coronavirus Disease‐19 (COVID‐19) has high mortality in kidney transplant recipients (KTR), and vaccination against severe acute respiratory syndrome‐coronavirus‐2 (SARS‐CoV‐2) is vital for this population. Although the humoral response to messenger RNA vaccines was shown to be impaired in KTR, there is a lack of data regarding the antibody response to inactivated vaccines. We investigated the antibody response to two consequent doses of the inactivated SARS‐CoV‐2 vaccine (CoronaVac; Sinovac Biotech, China). Methods: A total of 118 patients from two centers were included. The levels of anti‐SARS‐CoV‐2 immunoglobulin‐G antibodies against the nucleocapsid and spike antigens were determined with enzyme immunoassay (DIA.PRO; Milano, Italy) before the vaccine and one month after the second dose of the vaccine. Thirty‐three patients were excluded due to antibody positivity in the serum samples obtained before vaccination. Results: Eighty‐five patients, 47 of whom were female, with a mean age of 46 ± 12, were included in the statistical analysis. The maintenance immunosuppressive therapy comprised tacrolimus (88.2%), mycophenolate (63.6%), and low‐dose steroids (95.3%) in the majority of the patients. After a median of 31 days following the second dose of the vaccine, only 16 (18.8%) patients developed an antibody response. The median (IQR) antibody level was 52.5 IU/ml (21.5–96). Age (48 vs. 38, p = .005) and serum creatinine levels (1.14 vs. 0.91, p = .04) were higher in non‐responders and were also found to be independently associated with the antibody response (odds ratio (OR): 0.93, p = 0.012 and 0.15, p = 0.045, respectively) in multivariate analysis. Conclusion: In this study, we found the antibody response to the inactivated vaccine to be considerably low (18.8%) in KTR. Increased age and impaired renal function were associated with worse antibody response. Based on the knowledge that mRNA vaccines yield better humoral responses, this special population might be considered for additional doses of mRNA vaccination.